2018
DOI: 10.5380/rf.v48i3.50063
|View full text |Cite
|
Sign up to set email alerts
|

CONTROLLED RELEASE FERTILIZER IN THE GROWTH OF Moringa oleifera LAM. SEEDLINGS

Abstract: Moringa oleifera presents important medicinal properties, and its seeds are used to treat water for human consumption and wastewater. The aim of the present study was to analyze the initial growth of M. oleifera seedlings in enriched commercial substrate with differing doses of controlled release fertilizer. The experimental was designed in randomized blocks, with four repetitions of 16 seedlings each. The treatment used doses of controlled release fertilizer, with 0; 2; 4; 6; and 8 kg m -3 of commercial subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Navroski et al (2016) found that cedar seedlings (Cedrelafissilis) show good growth when 5 kg m -3 of CRF are incorporated into the substrate. Rosa et al (2018) verified improvement in growth of Moringa oleifera seedling when using controlled-release fertilizer at dose of 5.37 kg m -3 substrate.…”
Section: Variablementioning
confidence: 65%
“…Navroski et al (2016) found that cedar seedlings (Cedrelafissilis) show good growth when 5 kg m -3 of CRF are incorporated into the substrate. Rosa et al (2018) verified improvement in growth of Moringa oleifera seedling when using controlled-release fertilizer at dose of 5.37 kg m -3 substrate.…”
Section: Variablementioning
confidence: 65%
“…Navroski et al (2016) found that cedar seedlings (Cedrela fissilis) show good growth when 5 kg m -3 of CRF are incorporated into the substrate. For the production of seedlings of Moringa oleifera, Rosa et al (2018) found improvement in seedling growth when they used the controlled release fertilizer at a dose of 5.37 kg m -3 of substrate.…”
Section: Discussionmentioning
confidence: 99%
“…CRFs have been researched to have the optimal release of nutrients so that the rate of release of nutrients corresponds to the maximum rate of absorption of nutrients by plants, which varies dynamically during the stages of plant development during the growing season (IRFAN et al, 2018). For the production of Moringa oleifera seedlings, Rosa et al (2018) found improvement in seedling growth when they used the controlled-release fertilizer at a dose of 5.37 kg / m -3 of substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in Elaeis guineensis Jacq., the DQI value is 20.0, possibly due to different factors, including the increase in the crop growth rate, the positive effect of using plant growth-promoting rhizobacteria that alter the plant hormonal balance, and the improvement of both the crop yield and the plant quality biometric attributes [25]. In medicinal plants such as Moringa oleifera Lam., controlled-release fertilisers enhance plant vigour and quality, as shown by a DQI of 18.8 at a fertilisation dose of 5.37 kg m −3 of substrate [148] (Refs. in the Supplementary Materials).…”
Section: Dickson Quality Index Valuesmentioning
confidence: 99%